2017
DOI: 10.1186/s12939-017-0612-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of racial discrimination on the health of Australian Indigenous children aged 5–10 years: analysis of national longitudinal data

Abstract: BackgroundA growing body of literature highlights that racial discrimination has negative impacts on child health, although most studies have been limited to an examination of direct forms of racism using cross-sectional data. We aim to provide further insights on the impact of early exposure to racism on child health using longitudinal data among Indigenous children in Australia and multiple indicators of racial discrimination.MethodsWe used data on 1239 Indigenous children aged 5–10 years from Waves 1–6 (200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 55 publications
(69 reference statements)
6
83
0
Order By: Relevance
“…Racial discrimination of M aori and Australian Indigenous peoples and other minorities by health professionals and society is associated with a wide range of negative health outcomes in New Zealand and Australia. 40,114 Risk minimization policies and strategies…”
Section: Sids Epidemiologymentioning
confidence: 99%
“…Racial discrimination of M aori and Australian Indigenous peoples and other minorities by health professionals and society is associated with a wide range of negative health outcomes in New Zealand and Australia. 40,114 Risk minimization policies and strategies…”
Section: Sids Epidemiologymentioning
confidence: 99%
“…Whilst the reasons for this cannot be determined, it is possible that this might be driven by differences in study measures. For example, whereas we have reported on vicarious racism and reports of having doctor-diagnosed asthma with concurrent treatment, other studies have focussed on personally experienced racism, reported asthma ever in the child's lifetime (Shepherd et al, 2017) and phenotypic measures of asthma (Thakur et al, 2017). It is also possible that our definition of medicated asthma may have limited our ability to detect any potential association since it requires the children and their family to have access to healthcare, which we have shown is impacted by vicarious racism (Paine et al, 2018).…”
Section: Discussionmentioning
confidence: 91%
“…However, the relation between vicarious racism and mental health outcomes remains unclear. For example, a longitudinal study of indigenous Australian children (5 to 10 years) found that child or primary carer experiences of racism, discrimination, or prejudice were associated with poor mental health as measured on the Strengths and Difficulties questionnaire but that family experiences were not (Shepherd et al, 2017). In another Australian study (school students aged 8 to 15 years), Priest et al, (2017) reported no association between vicarious racism (students observing racism directed towards other students) on later depressive symptoms or loneliness, beyond the effect of direct experience of racism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility that cultural bias among physicians contributes to disparities in health care is increasingly recognised, but remains poorly investigated . Most research into racial prejudice and health care inequality has relied on self‐reports by patients, while Aboriginal communities have reported experiencing prejudice when accessing health care . Investigations of bias from the health care providers’ perspective are limited to a few qualitative studies based on personal attitude questionnaires, clinical vignettes, or experimental situations .…”
Section: Discussionmentioning
confidence: 99%